(untitled) (Journal of Health, Population and Nutrition, 2013)
Academic detailing is rarely practised in developing countries. A randomized control trial on healthcare service was conducted to evaluate the impact of academic detailing programme on the adherence of primary healthcare providers in Banke district, Nepal, to childhood diarrhoea treatment guidelines recommended by World Health Organization/United Nations Childrens Fund (WHO/UNICEF). The participants (N=209) were systematically divided into control and intervention groups. Four different academic detailing sessions on childhood diarrhoea management were given to participants in the intervention group. At baseline, 6% of the participants in the control and 8.3% in the intervention group were adhering to the treatment guidelines which significantly (p<0.05) increased among participants in the intervention (65.1%) than in the control group (16.0%) at the first follow-up. At the second follow-up, 69.7% of participants in the intervention group were adhering to the guidelines, which was significantly (p<0.05) greater than those in the control group (19.0%). Data also showed significant improvement in prescribing pattern of the participants in the intervention group compared to the control group. Therefore, academic detailing can be used for promoting adherence to treatment guidelines in developing countries, like Nepal. J HEALTH POPUL NUTR 2013 Jun; 31(2): 231-242 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16388